Teologi Reformis, Rasional dan Neo-Modern dalam Konteks Pertarungan Wacana Teologi Islam di Indonesia - Abubakar Eby Hara (Studia Islamika, 2002)
Fauzan Saleh's book, on Islamic theological discourses in Indonesia shows the dynamism of Islamic thoughts and practices in Indonesia. From Saleh's description, we may conclude that there have been efforts among Moslem theologians to reform Islamic theological thoughts so that they can cope with progress and modernity. The book focuses on three main modern theological trends: reformist, rationalist and neo-modernist discourses. The reformist was represented by two organizations: Muhammadiyah and Persatuan Islam (Persis), which attempted to purify Islamic teachings among Indonesian Moslems. For the theologians from these organizations, some practices and teachings of Islam adopted by Moslems did not reflect the true spirits of Islam, and were heavily influenced by local traditions such as Hinduism.DOI: 10.15408/sdi.v9i1.678